Organic Infrastructure vs. Inorganic Expansion: A Comparative Analysis of Capex-Led and Acquisition-Led Growth Strategies in Leading Indian Corporations (FY20–FY25). (Journal of Informatics Education and Research, 2026)
This research paper investigates the financial efficacy and risk profiles of two primary corporate growth trajectories: organic Capital Expenditure (Capex-Led) and inorganic business combinations (Acquisition-Led). Utilizing a five-year longitudinal dataset (FY20–FY25) of eleven blue-chip Indian entities—including Reliance Industries, Tata Group, and Infosys—the study employs rigorous statistical methodologies, including independent T-tests, linear regression models, and volatility assessments.Our findings indicate a statistically significant superior Return on Capital Employed (ROCE) for Acquisition-Led strategies (Mean ROCE: 33.8% vs. 11.3%, $p < 0.05$), which also demonstrate a higher revenue-to-investment multiplier (1.48x vs. 1.02x). However, this efficiency is counterbalanced by heightened earnings volatility (Standard Deviation: ~29% for inorganic growth). Conversely, Capex-Led strategies, while capital-intensive and subject to significant gestation lags, provide a more stable and predictable expansion path. The study concludes that while "Buying" growth offers immediate efficiency, "Building" growth remains essential for long-term industrial dominance.